A relação entre crenças e desenvolvimento de professores em um contexto comunicativo - Silva, Paulo Antônio Machado (2009)
The present research, which has an ethnographic orientation, aims at investigating the relationship between teachers beliefs and their development as teachers of English as a Foreign Language in the context of an institution which supposedly makes use of the communicative approach. The study was based on the observation of two newly-hired teachers in a private institute of English in the city of Niterói, in the Rio de Janeiro State, Brazil. These teachers went through a one-year training program, which was conducted by a mentor teacher. Their personal accounts of what they believe to be important when it comes to the learning and teaching of English, together with the close observation of their classroom practices and their own reflections and explanations both of their planning processes and the events in class provided the bulk of the data. The analysis of the data unveiled important clues to the understanding of the complex relationship between what teachers believe and what they actually do in the classroom, and how this relationship evolves throughout their training process. The hypotheses and the research questions for this research were grounded on recent studies about teachers beliefs, the theoretical principles of the communicative approach to language teaching and the theoretical study of metaphors, especially the conduit metaphor.